How far and how fast could Bitcoin fall? - Chung Baek (Privietlab, 2026)
Because Bitcoin typically exhibits higher volatility than traditional assets, evaluating and managing its risk is essential. We estimate Bitcoin’s potential maximum drawdowns (MDDs) using Monte Carlo simulations based on a stochastic jump process and assess the likelihood of substantial declines in the coming years. Based on our results, the simulation results suggest that an MDD of at least 60% is highly probable within three to four years, while an MDD of at least 70% appears plausible within five years. Moreover, our sensitivity analysis indicates that the MDD of Bitcoin is most strongly influenced by jump intensity. These results offer critical insights for market participants seeking to analyze Bitcoin’s downside risk and formulate strategies to navigate potential market downturns.